Current khat ( Catha edulis F.) use among Ethiopian women and its association with anemia and underweight: A cross-sectional analysis from Ethiopian Demographic and Health Survey - Amaha, ND; Kifle, MM; Mebrahtu, SG (Public Library of Science, 2024)
Background: Chewing fresh leaves of Catha edulis (khat) is a popular pastime activity among Ethiopians where 12% women chew it. Reports show that khat use has been associated with poor nutritional status. This study aimed to determine whether khat chewing is linked to underweight and anemia. Method: We analyzed data from the 2016 Ethiopian Demographic and Health Survey (EDHS). The EDHS used two stage stratified cluster sampling to collected data from 16,650 households. We used data from a total of 15,683 respondents and 1904 respondents who chewed ever chewed khat in their lives. We used Pearson’s chi-square, and logistic regression while stratifying by residence (urban vs rural) to control for confounders. Result: Our results indicated 10.7% (95%CI: 10.92,11.26) of women chewed khat for an average of 16.5 days in the previous month. A woman’s current khat chewing status was significantly associated with age, educational level, region, religion, wealth group, and marital status. Women aged 40–44 were significantly more likely to chew (AOR = 2.89,) compared to those aged 15–19. Compared with Protestant women, Muslim women were 210 times more likely (AOR = 210, 95% CI 102,435.7) to chew and women in the poorest wealth quintile had 73% higher odds (AOR = 1.73, 95% CI 1.22,2.44) of chewing khat when compared with the richest. Anemia was not associated with a woman’s chewing status, whereas rural women who chewed khat for more than 26 days in a month had a 78% increased risk (OR = 1.78) of being underweight when compared to non-chewers. Conclusion: Khat chewing is associated with sociodemographic factors and current khat use is associated with a higher risk of underweight among women living in rural areas. Implementing targeted awareness campaigns for women about the risks of khat chewing is recommended.